2007
DOI: 10.1063/1.2404794
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of confined electrically conducting carbon nanowires by heavy ion irradiation of fullerene thin film

Abstract: Conducting nanowires parallel to each other, embedded in fullerene matrix are synthesized by high energy heavy ion irradiation of thin fullerene film at low fluence (up to 5×1011ions∕cm2). The conductivity of the conducting zone is about seven orders of magnitude higher than that of the fullerene matrix. The conducting nanowires are evidenced by conducting atomic force microscopy. The typical diameter of the conducting tracks is observed to be about 40–100nm. The creation of conducting wires is explained by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 29 publications
0
41
2
Order By: Relevance
“…In addition the finite size of tip may have influence. Fourier transform infrared spectroscopy 18 has previously revealed that the track is surrounded by a polymerized annular cylindrical region. The carbon nanowires are predominantly parallel to each other and perpendicular to the substrate, because the irradiation has been performed perfectly perpendicular to fullerene films.…”
Section: Methodsmentioning
confidence: 99%
“…In addition the finite size of tip may have influence. Fourier transform infrared spectroscopy 18 has previously revealed that the track is surrounded by a polymerized annular cylindrical region. The carbon nanowires are predominantly parallel to each other and perpendicular to the substrate, because the irradiation has been performed perfectly perpendicular to fullerene films.…”
Section: Methodsmentioning
confidence: 99%
“…The same effect has been observed in fullerenes. 106 Normally the tracks are well aligned with respect to the beam directions and themselves can be viewed as nanostructures inside bulk materials. The track cores can be etched away and filled with some other material, which enables production of long straight NWs.…”
Section: A Production Of Defects In Bulk Targetsmentioning
confidence: 99%
“…Low-dose irradiation also gave rise to another interesting phenomenon: conducting NWs parallel to each other, embedded in fullerene matrix were synthesized by high energy heavy ion bombardment of thin fullerene films. 106 The typical diameter of the conducting tracks was about 40-100 nm. The creation of conducting wires could be explained by transformation of fullerene to conducting forms of carbon in the ion track, surrounded by the polymerized zone.…”
Section: Ion Irradiation Of Fullerenes and Fullerene-nanotube Systemsmentioning
confidence: 99%
“…The field emission properties of these conducting nanowires were also undertaken 44 . 45 , resulting in formation of Si nanocrystals in the film. This was investigated by PL and TEM.…”
Section: Generation Of C Nanowire Like Structuresmentioning
confidence: 99%